1992
DOI: 10.1063/1.463746
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced interaction of ammonia with GaAs(100). II. Desorption dynamics

Abstract: UV laser irradiation of ammonia adsorbed on GaAs(100) leads to molecular desorption, with a mean translational temperature of <Etrans/2k≳=300 K, independent of photon energy and isotope substitution. However, the photodesorption cross section depends strongly on isotope substitution: σNH3/σND3=4.1 at hν=6.4 eV. This isotope effect is too large to be accounted for by the mass difference in the leaving particles (NH3 vs ND3), but can be successfully explained in terms of an isotope effect in the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This is difficult to realize because the adsorbate−surface bond is viewed as part of a delocalized surface electronic structure and relaxation of electronic excitation energy on surfaces is extremely efficient . Nearly all photodesorption studies point to indirect mechanisms, e.g., those due to hot substrate carriers or to the transfer of intramolecular excitation to the desorption coordinate. The best example for the latter is the vibrationally mediated UV photodesorption mechanism for ammonia from semiconductor and metal surfaces, as discovered by Zhu et al and explored by a number of other groups. Recently, Matsumoto and co-workers reported that the photochemistry, including desorption and dissociation, of methane weakly adsorbed on Pt(111) resulted from adsorbate-localized optical excitation . However, photodesorption in this case is likely due to intramolecular excitation rather than direct excitation of the adsorbate−surface bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is difficult to realize because the adsorbate−surface bond is viewed as part of a delocalized surface electronic structure and relaxation of electronic excitation energy on surfaces is extremely efficient . Nearly all photodesorption studies point to indirect mechanisms, e.g., those due to hot substrate carriers or to the transfer of intramolecular excitation to the desorption coordinate. The best example for the latter is the vibrationally mediated UV photodesorption mechanism for ammonia from semiconductor and metal surfaces, as discovered by Zhu et al and explored by a number of other groups. Recently, Matsumoto and co-workers reported that the photochemistry, including desorption and dissociation, of methane weakly adsorbed on Pt(111) resulted from adsorbate-localized optical excitation . However, photodesorption in this case is likely due to intramolecular excitation rather than direct excitation of the adsorbate−surface bond.…”
Section: Introductionmentioning
confidence: 99%
“…7 Nearly all photodesorption studies point to indirect mechanisms, e.g., those due to hot substrate carriers or to the transfer of intramolecular excitation to the desorption coordinate. [8][9][10] The best example for the latter is the vibrationally mediated UV photodesorption mechanism for ammonia from semiconductor and metal surfaces, as discovered by Zhu et al [11][12][13] and explored by a number of other groups. [14][15][16][17] Recently, Matsumoto and co-workers reported that the photochemistry, including desorption and dissociation, of methane weakly adsorbed on Pt(111) resulted from adsorbate-localized optical excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Isotope effects suggested desorption from a hot ground state. 233 The same group described the substrate excited photochemical decomposition of AsH3 on G a A ~( l 0 0 ) . ~~~ Bimolecular adsorbate photochemistry was considered by Matsumoto and coworkers, who studied N 2 0 and co-adsorbed N 2 0 / 0 2 on Pt( 1 1 1).…”
Section: Adsorbate Laser Chemistrymentioning
confidence: 99%
“…For instance, the lifetime of the C-O stretching vibration on Pt(111) is 2.2 ps [14], whereas that of CO on Si(001) is 1.87 ns [15,16]. The latter longer lifetime suggests that the accumulated energy would overcome the reaction barrer, but the observed rate in vibration-induced reaction follows a linear relation on a semiconductor [17]. Because the mechanism is still unclear, we focus in this work on the role of covalent electronic states localized near the molecule adsorbed on the surface.…”
Section: Introductionmentioning
confidence: 99%